Wide distribution of carbapenem resistant Acinetobacter baumannii in burns patients in Iran - Farshadzadeh, Zahra; Hashemi, Farhad B.; Rahimi, Sara; Pourakbari, Babak; Esmaeili, Davoud; Haghighi, Mohammad A.; Majidpour, Ali; Shojaa, Saeed; Rahmani, Maryam; Gharesi, Samira; Aziemzadeh, Masoud; Bahador, Abbas (Frontiers in Microbiology, 2015)
Antimicrobial resistance in carbapenem non-susceptible Acinetobacter baumannii (CNSAb) is a major public health concern globally. This study determined the antibiotic resistance and molecular epidemiology of CNSAb isolates from a referral burn center in Tehran, Iran. Sixty-nine CNSAb isolates were tested for susceptibility to antimicrobial agents using the E-test methodology. Multiple locus variable number tandem repeat analysis (MLVA), Multilocus sequence typing and multiplex PCR were performed. PCR assays tested for ambler classes A, B, and D β-lactamases. Detection of ISAba1, characterization of integrons, and biofilm formation were investigated. Fifty-three (77%) isolates revealed XDR phenotypes. High prevalence of blaOXA-23-like (88%) and blaPER-1 (54%) were detected. ISAba1 was detected upstream of blaADC, blaOXA-23-like and blaOXA51-like genes in, 97, 42 and 26% of isolates, respectively. Thirty-one (45%) isolates were assigned to International Clone (IC) variants. MLVA identified 56 distinct types with 6 clusters and 53 singleton genotypes. Forty previously known MLST sequence types forming 5 clonal complexes were identified. The Class 1 integron (class 1 integrons) gene was identified in 84% of the isolates. The most prevalent (33%) cassette combination was aacA4-catB8-aadA1. The IC variants were predominant in the A. baumannii lineage with the ability to form strong biofilms. The XDR-CNSAb from burned patients